Agama pra Islam di Nusantara dan Karakteristik Budayanya - Najwa Atthaillah; Jahwa Hikmatun Nisa (-, 2026)
This study aims to identify the forms of pre-Islamic religious systems in the Indonesian archipelago and to analyze the cultural characteristics that emerged from these beliefs. The main issue examined is how indigenous belief systems, such as animism and dynamism, integrated with Hindu-Buddhist influences to shape a unique cultural identity prior to the arrival of Islam. This research employed a qualitative method with historical and phenomenological approaches through a literature review of classical manuscripts and archaeological remains. The findings indicate that pre-Islamic communities in the archipelago exhibited a high degree of religious syncretism, in which local ancestor worship harmoniously blended with major religious traditions originating from India. These beliefs were manifested in distinctive cultural characteristics, including the construction of megalithic structures, the sacralization of nature, and complex communal rituals. The study concludes that these pre-Islamic foundations provided a strong cultural framework that later influenced the Islamization process, resulting in a distinctive form of Indonesian Islam characterized by pluralism and deeply rooted local wisdom